بناء إنموذج رياضي لتعظيم عائد الشركة الإنتاجية بإستعمال البرمجة الكسرية الخطية الصحيحة – مع تطبيق عملي - بخيت, عبد الجبار خضر; حسين, فاطمة عبدالباري (Journal of Economics and Administrative Sciences, 2014)
These search summaries in building a mathematical model to the issue of Integer linear Fractional programming and finding the best solution of Integer linear Fractional programming (I.L.F.P) that maximize the productivity of the company,s revenue by using the largest possible number of production units and maximizing denominator objective which represents,s proportion of profits to the costs, thus maximizing total profit of the company at the lowest cost through using Dinkelbach algorithm and the complementary method on the Light industries company data for 2013 and comparing results with Goal programming methods results.It is clear that the final results of resolution and Dinkelbach algorithm and complementary method are very near and maximizing proportion is equal, while, Goal programming methods are less.From this, we can exclude that the Integer linear Fractional programming considers the best one, this result is logical because goal programming is trying to create harmony to achieve the goal of contrasting, This is considered as a model in the model to maximize the return on any company productivity.